The Association Between Longevity-Associated FOXO3 Allele and Heart Disease in Septuagenarians and Octogenarians: The SONIC Study. Issue 8 (13th July 2021) - Klinpudtan, Nonglak; Allsopp, Richard C; Kabayama, Mai; Godai, Kayo; Gondo, Yasuyuki; Masui, Yukie; Akagi, Yuya; Srithumsuk, Werayuth; Sugimoto, Ken; Akasaka, Hiroshi; Takami, Yoichi; Takeya, Yasushi; et al.
Abstract: The G allele of FOXO3 gene (single-nucleotide polymorphism; rs2802292) is strongly associated with human longevity. However, knowledge of the effect of FOXO3 in older populations, men or women, with heart disease is limited. This cross-sectional study in Japan included 1836 older adults in the 70- and 80-year-old groups. DNA samples isolated from buffy coat samples of peripheral blood were used to genotype FOXO3 (rs2802292). Self-reports were used to obtain heart disease data according to physician diagnosis. Multiple logistic regression was used to test the association by adjusting for the traditional risk factor of heart disease. The prevalence of heart disease in women FOXO3 G-allele carriers was higher than noncarriers (16.7% vs 11.6%, p = .022). The prevalence of coronary heart disease was lower for FOXO3 G carriers in the 70-year-old group for both sexes (men: 9.3% vs 4.3%, p = .042 and women: 10% vs 9%, p = .079, respectively). The G allele was negatively associated with heart disease after adjusting for diabetes, hypertension, dyslipidemia, and smoking in men (odds ratio [OR] = 0.70, 95% confidence intervals [CIs], 0.49–0.99, p = .046), although the association was weaker after full adjustment. In contrast, women carriers of the FOXO3 G allele showed a positive association with heart disease after total adjustment (OR = 1.49, 95% CI, 1.00–2.21, p = .049). In conclusion, the longevity-associated G allele of FOXO3 was observed to have contrasting associations with heart disease prevalence according to sex in older Japanese. To further confirm this association, a longitudinal study and a large sample size will be required.